Structures of glyceraldehyde 3‐phosphate dehydrogenase in Neisseria gonorrhoeae and Chlamydia trachomatis. (28th January 2020) - Barrett, Kayleigh F.; Dranow, David M.; Phan, Isabelle Q.; Michaels, Samantha A.; Shaheen, Shareef; Navaluna, Edelmar D.; Craig, Justin K.; Tillery, Logan M.; Choi, Ryan; Edwards, Thomas E.; Conrady, Deborah G.; Abendroth, Jan; et al.
Abstract: Neisseria gonorrhoeae ( Ng ) and Chlamydia trachomatis ( Ct ) are the most commonly reported sexually transmitted bacteria worldwide and usually present as co‐infections. Increasing resistance of Ng to currently recommended dual therapy of azithromycin and ceftriaxone presents therapeutic challenges for syndromic management of Ng ‐ Ct co‐infections. Development of a safe, effective, and inexpensive dual therapy for Ng ‐ Ct co‐infections is an effective strategy for the global control and prevention of these two most prevalent bacterial sexually transmitted infections. Glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) is a validated drug target with two approved drugs for indications other than antibacterials. Nonetheless, any new drugs targeting GAPDH in Ng and Ct must be specific inhibitors of bacterial GAPDH that do not inhibit human GAPDH, and structural information of Ng and Ct GAPDH will aid in finding such selective inhibitors. Here, we report the X‐ray crystal structures of Ng and Ct GAPDH. Analysis of the structures demonstrates significant differences in amino acid residues in the active sites of human GAPDH from those of the two bacterial enzymes suggesting design of compounds to selectively inhibit Ng and Ct is possible. We also describe an efficient in vitro assay of recombinant GAPDH enzyme activity amenable to high‐throughput drug screening to aid in identifying inhibitory compounds and begin to address selectivity.